2005
DOI: 10.1016/j.devcel.2005.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Autoregulation and Homodimerization Are Involved in the Activation of the Plant Steroid Receptor BRI1

Abstract: The leucine-rich-repeat receptor serine/threonine kinase, BRI1, is a cell-surface receptor for brassinosteroids (BRs), the steroid hormones of plants, yet its activation mechanism is unknown. Here, we report a unique autoregulatory mechanism of BRI1 activation. Removal of BRI1's C terminus leads to a hypersensitive receptor, indicated by suppression of dwarfism of BR-deficient and BR-perception mutants and by enhanced BR signaling as a result of elevated phosphorylation of BRI1. Several sites in the C-terminal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
309
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 263 publications
(323 citation statements)
references
References 44 publications
(4 reference statements)
12
309
0
2
Order By: Relevance
“…The second hypothesis is supported by a recent study from Joanne Chory's lab, which provided evidence that receptor activation involves ligand induced conformation changes in the BRI1 kinase [29]. In this study, deletion of the C-terminal 40 amino acids (CT) of BRI1 was shown to increase receptor activity, as indicated by increased phosphorylation of BRI1 and growth response in transgenic plants expressing such truncated BRI1 receptor [29].…”
Section: Br Activation Of Bri1 and Bak1 Receptor Kinasesmentioning
confidence: 78%
See 4 more Smart Citations
“…The second hypothesis is supported by a recent study from Joanne Chory's lab, which provided evidence that receptor activation involves ligand induced conformation changes in the BRI1 kinase [29]. In this study, deletion of the C-terminal 40 amino acids (CT) of BRI1 was shown to increase receptor activity, as indicated by increased phosphorylation of BRI1 and growth response in transgenic plants expressing such truncated BRI1 receptor [29].…”
Section: Br Activation Of Bri1 and Bak1 Receptor Kinasesmentioning
confidence: 78%
“…Although the model of Wang et al [29] is consistent with most of the observations, many questions remain to be answered. For example, the possibility that activation of BRI1 kinase requires dimerization with BAK1 has yet to be tested experimentally.…”
Section: Br Activation Of Bri1 and Bak1 Receptor Kinasesmentioning
confidence: 84%
See 3 more Smart Citations